2021
DOI: 10.1002/cmdc.202000874
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Inhibitor of Human Purine Nucleoside Phosphorylase by a Simple Hydrophilic Interaction Liquid Chromatography Enzymatic Assay

Abstract: Human purine nucleoside phosphorylase (HsPNP) belongs to the purine salvage pathway of nucleic acids. Genetic deficiency of this enzyme triggers apoptosis of activated T-cells due to the accumulation of deoxyguanosine triphosphate (dGTP). Therefore, potential chemotherapeutic applications of human PNP inhibitors include the treatment of T-cell leukemia, autoimmune diseases and transplant tissue rejection. In this report, we present the discovery of novel HsPNP inhibitors by coupling experimental and computatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
3
5
0
Order By: Relevance
“…1A], a value similar to that reported by Chern et al (1993). While this work was in progress, Rabuffetti et al (2021) reported that 8-aminoinosine is a competitive inhibitor of rhPNPase, with a Ki of 48 mmol/L. Indeed, we also observed that 8-aminoinosine reduced the activity of rhPNPase (with inosine as substrate) in a manner consistent with competitive inhibition (Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…1A], a value similar to that reported by Chern et al (1993). While this work was in progress, Rabuffetti et al (2021) reported that 8-aminoinosine is a competitive inhibitor of rhPNPase, with a Ki of 48 mmol/L. Indeed, we also observed that 8-aminoinosine reduced the activity of rhPNPase (with inosine as substrate) in a manner consistent with competitive inhibition (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Independent of our studies, Rabuffetti et al (2021) also observed that 8-aminoinosine is an inhibitor of PNPase, and their kinetic analysis suggested that 8-aminoinosine is a competitive inhibitor of this enzyme. Our results indicate that 8-aminoinosine’s ability to block PNPase activity likely involves two mechanisms.…”
Section: Discussionsupporting
confidence: 69%
“…Human purine nucleoside phosphorylase ( h PNP) belongs to a family of enzymes involved in the purine salvage pathway of nucleoside biosynthesis, which promotes the utilization of purine bases [ 1 ]. Its primary role is to catalyze the cleavage of inosine, 2’-deoxyinosine, guanosine and 2’-deoxyguanosine (dG) to the corresponding base and sugar-1-phosphate via reversible phosphorolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, h PNP inhibitors are used in organ transplant surgeries to provide an immunodeficiency status during and after the procedure. In some cases, h PNP inhibitors are also able to enhance the activity of antiviral and antitumor nucleoside drugs [ 1 , 4 ] by inhibiting the premature metabolism of the nucleoside drug. All of these reasons explain the great interest in studying the structure of human purine nucleoside phosphorylase and the continued search for more effective inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation